Pork slaughterhouses and vendors sustain hygiene practices, while multi-sectoral collaboration strengthens One Health adoption for food safety in Vietnam - Le Thi Huyen Trang; Dang Xuan Sinh; Unger, Fred; Hung Nguyen-Viet (International Livestock Research Institute, 2025)
Here we report 21 slaughterhouses across six provinces in Vietnam continuing to use of stainless-steel grid for slaughter, keep following the trained hygiene practices (7), and scale-out the same intervention package (14). The sustained application of these practices at slaughterhouses has strengthened routine food safety management. At market level, we report the adoption of the intervention package by 60 pork vendors in Dien Bien and Son La provinces, resulting in substantial and measurable reductions in Salmonella prevalence from 60% to 47% in Dien Bien, and from 83% to 60% in Son La. These reductions demonstrate the effectiveness, transferability, and public health relevance of the approach when implemented beyond the original project sites. In parallel, we also report the outcome of further advanced multi-sectoral collaboration and enhanced food safety risk-based management in Vietnam through the support of SAAF-AoW3 to Food Safety Technical Working Group under the Vietnam One Health Partnership for Zoonoses. In 2025, One Health education and operationalization was also strengthened by continuing to use the One Health field site for practical learning and field-based activities related to food safety, zoonoses and antimicrobial resistance (AMR), reaching over 80 university students and lecturers, across disciplines of veterinary medicine, food technology, public health.